Enhancing Operational Team Capacity for Gen-Z Retention in a Digital Transformation Context - Wibowo, Firdaus Andi; Yulianto, Tomi (International Journal of Educational Research Excellence, 2026)
The rapid adoption of digital transformation necessitates a strategic approach to Human Capital Management (HCM). Organizations must align workforce competencies with transformation goals to retain and develop Gen-Z talent, a digitally adept and innovation-driven demographic. This study employs the HC Framework-8 elements to analyze organizational structure, identify skill gaps, and implement strategies that enhance Gen-Z retention in the digital transformation era. The findings suggest that competency-based planning, targeted learning programs, and flexible engagement strategies are crucial in sustaining a digitally ready workforce.